Analysis of The Influence of Liquidity, Sales, Growth, and Working Capital Turnover on Profitability (Study on Technology Sector Companies Listed on the Indonesia Stock Exchange for the 2021-2024 Period) - Nur Fadhilah; Elok Vilantika (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
In the rapid development of the digital era in Indonesia, the growth of the technology sector poses challenges to the level of profitability of companies, due to changes in liquidity value, sales growth and working capital turnover. This study aims to analyze these three factors on the profitability of technology sector companies listed on the Indonesia Stock Exchange. The population of this study is technology companies listed on the Indonesia Stock Exchange for the 2021-2024 period. The sample of this study was selected by the Purposive Sampling method. A total of 35 companies that passed the criteria were used as samples. The method used is a quantitative approach through multiple linear regression analysis with the help of spss software applications with secondary data from financial statements. The results of this study show that the liquidity variable has a negative effect, while sales growth and working capital turnover have a positive effect on profitability. In conclusion, it shows the importance of optimal liquidity management and increased sales and working capital efficiency to improve financial performance in order to create stable income in the midst of competition in the technology industry.